Inflammatory biomarkers as prognostic indicators for liver cirrhosis - Naglaa Abou-Elfattah Tawfik; Naglaa A El-Gendy; Hanaa Abou Elyazid Abou Elhassan; Eman Elshohat Ebrihem; Rayyh Abdelazeem M Saleh (Wolters Kluwer Medknow Publications, 2019)
Background Severity of liver cirrhosis is commonly assessed by Child-Pugh and model of end-stage liver disease (MELD) scores, which reflect liver dysfunction mainly and do not assess associated systemic events, which influence the failure of other organs. Aim To study the role of serum level of copeptin (CPP) and high-sensitivity C-reactive protein (hsCRP) as indicators of prognosis in liver cirrhosis and compare these results with usual prognostic scores, raising the importance of proper management of systemic infections in cirrhotic patients to prevent cirrhosis progression. Patients and methods A cross-sectional study was carried out on 80 cirrhotic patients, who were classified into four equal groups: Child A, B, C, and Child C with systemic infections. Serum CPP and hsCRP were measured by enzyme-linked immunosorbent assay technique. Results There was a statistically significant increase in CPP serum levels among cirrhotic patients [9.70 (7.70-14.30)] in comparison with its serum level in healthy participants [5.95 (5.40-6.75)]. There were gradually increases of CPP serum levels through Child-Pugh A, B, and C groups [6.40 (5.42-8.05), 10.15 (7.75-14.20), and 13.05 (8.77-17.27), respectively] in comparison with the control group. There were positive correlations of CPP with MELD score, Child-Pugh, and hsCRP (r=0.60, 0.71, and 0.60, respectively, P<0.000). There was a significantly increase in serum level of hsCRP among cirrhotic patients [9.90 (7.12-16.67)] than control group [2.50 (1.67-5.91)]. Its median values and interquartile range concentrations were the lowest among healthy group and increased gradually through Child-Pugh A, B, and C and Child-Pugh C with infection groups [2.50 (1.67-5.91), 7.15 (6.32-9.45), 8.35 (7.12-12.17), 9.20 (6.95-13.15), and 20.35 (14.85-32.22), respectively] (P=0.000). There were significant positive correlations of hsCRP with CPP, MELD score, and Child-Pugh (r=0.51, 0.54, and 0.75, respectively). Conclusion CPP and hsCRP serum levels can be used as prognostic indicators of liver cirrhosis and account for systemic infections involved in deterioration of liver cirrhosis.